Sound transmission loss of double-wall piezoelectric plate made of functionally graded materials via third-order shear deformation theory. (1st July 2019) - Danesh, Masood; Ghadami, Abbas
Abstract: According to the third-order shear deformation assumption, this paper analytically investigates the sound transmission loss (STL) through a rigidly baffled finite rectangular double wall piezoelectric plate structure made of functionally graded materials (FGMs) with enclosed acoustic cavity, under harmonic plane sound excitation and initial external electric voltage. The effective piezoelectric material properties of each plate are supposed to be continuously variable across the thickness direction using a power law model in terms of the volume fractions of the material phases. The coupled vibroacoustic governing equations are achieved utilizing Hamilton's principle and then solved analytically by applying the sound velocity potential method in conjunction with double Fourier series expansions to determine STL equation. Numerical studies are performed to illustrate the effects of the acoustic cavity depth, initial external electric voltage, incident elevation angle, gas type used in acoustic cavity, and material gradient on the changes of STL curves of simply supported double wall FGM piezoelectric plate. The profound effect of these factors on sound isolation performance is clearly shown.